A nurse‐led atrial fibrillation clinic: Impact on anticoagulation therapy and clinical outcomes. Issue 12 (25th August 2020) - Rivera‐Caravaca, José Miguel; Gil‐Perez, Pablo; Lopez‐García, Cecilia; Veliz‐Martínez, Andrea; Quintana‐Giner, Miriam; Romero‐Aniorte, Ana Isabel; Fernandez‐Redondo, Concepción; Muñoz, Luis; Quero, Eva; Esteve‐Pastor, María Asunción; Lip, Gregory Y. H.; Roldán, Vanessa; et al.
Abstract: Background: Nurses play a central role in the management of atrial fibrillation (AF) patients. An unresolved question is whether a nurse‐led clinic would improve clinical outcomes. Herein, we investigated the impact of a nurse‐led clinic on anticoagulation therapy and clinical outcomes in a cohort of naïve AF patients. Methods: Prospective study including AF patients starting vitamin K antagonists (VKAs) into a nurse‐led AF clinic. These patients were followed in this specific AF clinic. Additionally, AF patients already taking VKAs for 6 months followed according to the routine clinical practice were included as comparison group. The quality of anticoagulation was assessed at 6 months. Efficacy and safety endpoints were recorded during follow‐up. Results: We included 223 patients (Nurse‐led clinic: 107; Usual care: 116). The mean time in therapeutic range and the proportion of INRs within the therapeutic range were similar in both groups. During 2.06 (IQR 1.01‐2.94) years of follow‐up, 64 (28.7%) patients changed to direct‐acting oral anticoagulants. The proportion of switchers was higher in the nurse‐led clinic (37.4%) than in the usual care group (20.7%) ( P  = .006) and these patients spent less time to switch (2.0 [IQR 0.7‐2.9] vs 6.0 [IQR 3.7‐11.2] years; P  < .001). Importantly, the annual rate of ischaemic stroke/TIA was significantly lower in the nurse‐led clinic (0.47%/year vs 3.88%/year, P  = .016), without differences in safety endpoints. Conclusion: A nurse‐led AF clinic may offer a "patient‐centered" review and holistic follow‐up, and it would be associated with a reduction of ischaemic stroke/TIA, without increasing bleeding complications. Further studies should confirm these results.